Cooperative breeders adjust offspring sex ratios to produce helpful helpers - Griffin, A; Sheldon, B; West, S (University of Chicago Press, 2005)
Whether birds and mammals adaptively adjust their offspring sex ratio in response to their environment is much debated. A source of confusion is that different studies show different patterns, with sex ratio adjustment appearing to occur in some cases but not others. The extent to which this reflects interesting biological variation due to differences in the underlying selective forces, as opposed to statistical noise, is not clear. Cooperatively breeding species offer an opportunity to address this problem because the strength of selection on sex ratio adjustment can be estimated. When helping behavior is sex dependent, parents are predicted to overproduce the helping sex when this sex is rare or absent. We show here that the extent of this behavior depends on the benefit that helpers bring to parents: there is greater sex ratio adjustment when helpers bring larger benefits. Variable selection on sex ratio adjustment may thus explain variable empirical findings.